Retention Characteristics and DMP Efficiency in V-NAND With Dimple Structure - Seongwoo Kim; Gunwook Yoon; Seungjae Baik; Myounggon Kang (IEEE Journal of the Electron Devices Society, 2025)
In this paper, we analyze the retention characteristics of vertical NAND(V-NAND) with dimpled (convex and concave) structures considering the impact of adjacent cell states. Additionally, we assess the efficiency of the previously proposed dummy cell program (DMP) in improving retention characteristics. Our results indicate that when the adjacent cell is in the erased state, the retention characteristics of the target cell are affected by conduction band $(E_{C})$ variations due to trapped electrons. The concave structure shows the best retention characteristics, whereas the convex structure shows the most degradation. This difference becomes even more pronounced when the adjacent cell is in the programmed state. However, when DMP is applied to the convex structure, which exhibits the most degraded retention characteristics, the greatest improvement is observed due to significant changes in channel potential $(V_{ch})$ caused by the fast-programming speed.